Synthetic peptides from two Pf sporozoite invasion-associated proteins specifically interact with HeLa and HepG2 cells (2011)
Two recently described molecules have been associated with sporozoite traversal ability and hepatocyte entry: sporozoite invasion-associated proteins (SIAP)-1 and -2. The HeLa and HepG2 cell binding ability of synthetic peptides spanning the whole SIAP-1 and -2 sequences has been studied in the search for identifying these proteins' functionally active specific regions. Twelve HepG-2 and seventeen HeLa cell high-activity binding peptides (HABPs) have been identified in SIAP-1, 8 of them having high specific binding affinity for both cell lines. Four HepG2 HABPs and two HeLa HABPs have been identified in SIAP-2, one of them interacting with both HeLa and HepG2 cells. SIAP-1 and SIAP-2 HABPs bound specifically and saturably to heparin sulfate and chondroitin sulfate-type membrane receptors on host cells. Circular dichroism assays have shown high ?-helix content in SIAP-1 and SIAP-2 HABP secondary structure. Immunofluorescence analysis has revealed that specific peptides against SIAP proteins are highly immunogenic in mice and that anti-SIAP-1 and -2 antibodies recognize the native protein in Plasmodium falciparum sporozoites. Polymorphism studies have shown that a most SIAP-1 and -2 HABPs are conserved among P. falciparum strains. Our results have suggested that SIAP-1 and -2 participate in host-pathogen interactions during cell-traversal and hepatocyte invasion and highlighted the relevance of the ongoing identification and study of potentially new molecules when designing a fully protective antimalarial vaccine. © 2011 Elsevier Inc.